Heparan sulfate 3-O-sulfotransferase 4 is genetically associated with herpes zoster and enhances varicella-zoster virus–mediated fusogenic activity. (16th November 2021) - Ohka, Seii; Yamada, Souichi; Nishizawa, Daisuke; Fukui, Yoshiko; Arita, Hideko; Hanaoka, Kazuo; Iseki, Masako; Kato, Jitsu; Ogawa, Setsuro; Hiranuma, Ayako; Kasai, Shinya; Hasegawa, Junko; et al.
Acute pain that is associated with herpes zoster (HZ) can become long-lasting neuropathic pain, known as chronic post-herpetic neuralgia (PHN), especially in the elderly. HZ is caused by the reactivation of latent varicella-zoster virus (VZV), whereas PHN is not attributed to ongoing viral replication. Although VZV infection reportedly induces neuronal cell fusion in humans, the pathogenesis of PHN is not fully understood. A genome-wide association study (GWAS) revealed significant associations between PHN and the rs12596324 single-nucleotide polymorphism (SNP) of the heparan sulfate 3- O -sulfotransferase 4 ( HS3ST4 ) gene in a previous study. To further examine whether this SNP is associated with both PHN and VZV reactivation, associations between rs12596324 and a history of HZ were statistically analyzed using GWAS data. HZ was significantly associated with the rs12596324 SNP of HS3ST4, indicating that HS3ST4 is related to viral replication. We investigated the influence of HS3ST4 expression on VZV infection in cultured cells. Fusogenic activity after VZV infection was enhanced in cells with HS3ST4 expression by microscopy. To quantitatively evaluate the fusogenic activity, we applied cytotoxicity assay and revealed that HS3ST4 expression enhanced cytotoxicity after VZV infection. Expression of the VZV glycoproteins gB, gH, and gL significantly increased cytotoxicity in cells with HS3ST4 expression by cytotoxicity assay, consistent with the fusogenic activity as visualized by fluorescence microscopy. HS3ST4 had little influence on viral genome replication, revealed by quantitative real-time polymerase chain reaction. These results suggest that HS3ST4 enhances cytotoxicity including fusogenic activity in the presence of VZV glycoproteins without enhancing viral genome replication.